emotion and religous behaviour relation according to psychologist - Mustaffa , Nor Nazimi Mohd; Ismail, Amnah Saayah (International Journal of Psychosocial Rehabilitation, 2020)
Emotions play an important role in assessing one’s behaviour and actions, including religious acts. In the field of religious psychology, the term ‘religious behaviour’ is applied to describe the specific human behaviour associated with religion. Religious behaviour is an outward reaction by people based on their belief in the divine power of God or the concepts embraced by the religion. Put simply, religious behaviour reflects the statement of one’s religious life and religious awareness. Religious behaviour encompasses all aspects of the human life and not limited to the divine aspects linked with ritual practice, but includes all aspects related to human relationships. Religious behaviour must be based on religion, and in line with the teachings of the religion that are not in conflict with it. Hence, the question that arises is, ‘how human emotions are related to religious behaviour in everyday life?’ As such, this study examined how emotions are related to religious behaviour. This study adopted the qualitative approach by performing document content analysis that incorporated data reduction, data presentation, and conclusion. This study had synthesised Freud’s classic work and the contemporary works from Feierman to achieve the objectives. As a result, emotion displayed a relationship with religious behaviour expressed by humans. Emotions and feelings of love, jealousy, fear, curiosity, and awe stem from expression of religious behaviour. Freud and Feierman asserted that these emotions and feelings are the cause of human tendency to fulfil their needs in a way that reveals a figure that God considers and should be worshipped.